The Necessity of Management Team Formation and Its Effect on Civil Engineering Projects Success - Mehdi Bahadori Kosanji Zare; Alireza Mirjalili; Mohammad Mirabi (Salehan Institute of Higher Education, 2016)
Success of a project is one of the greatest and most important goals and concerns of mangers and all people involved in a project. The purpose of state civil engineering projects success is to decrease cost and time as well as increasing the quality and satisfaction of society and government as the main customers. Many factors influence civil engineering projects success and identifying them highly help the successful implementation of civil engineering projects. As one of the most important factor, it can be referred to project management team. The main purpose of the present study is to find the effective relation between management team formation and civil engineering projects success. To this end, library and field methods have been used. To gather required data, a 15-item questionnaire has been employed and distributed among 30 managers of successful state projects, including employer, consultant and contractor. The obtained data has been analyzed using descriptive method. As the findings revealed, weakness of managerial factors avoids complete success of state civil engineering projects implementation. The study also has concluded that team formation is highly important to organize project; management team enabling is regarded necessary for organizational projects success, and work relation of team members plays an important role in project management success.